Influence of microwave irradiation on kinetics and thermodynamics of extraction of flavonoids from Phyllanthus emblica - Krishnan,R. Yedhu (2017)
Abstract-The effects of solvent-to-feed (S) and temperature (T) on the kinetics and thermodynamics of the microwave assisted extraction (MAE) of flavonoids from dried fruits of Phyllanthus emblica using water as solvent have been studied. The flavonoid concentration - time data was analyzed using second order and diffusion models. Both the temperature and solvent-to-feed ratio influenced the initial extraction rate and equilibrium concentration. Biot numbers were found to be greater than 50, implying that the internal mass transfer was the rate controlling step in MAE. The composition of extracts obtained using MAE and conventional extraction was similar. However, the effective diffusion coefficients were doubled in MAE when compared to conventional extraction. An empirical correlation was developed to predict the kinetics of MAE as a function of solvent-to-feed ratio and temperature. The study will be of interest to food and pharmaceutical industries.